ANALISIS PENGARUH VOLATILITAS NILAI TUKAR TERHADAP KINERJA KEUANGAN PADA INDUSTRI PERBANKAN DI INDONESIA - Hendrawan, Agus (Media Riset Bisnis Ekonomi Sains dan Terapan, 2025)
ABSTRACTThis paper analyzes the impact of Rupiah exchange rate fluctuations (against USD, JPY, and EUR) on the banking performance in Indonesia. We apply four proxies for bank performance: the intermediation function measured by the Loan-to-Deposit Ratio (LDR), and profitability measured by income from spot derivative transactions (INCSD). In addition to exchange rates, we incorporate bank-specific characteristics, including total assets (ASSET) and loan loss provisions (Provision), as well as macroeconomic variables such as GDP growth, interbank rates (JIBOR), and inflation—following recent frameworks by Nguyen et al. (2022) and Fanta et al. (2021). The dataset includes all commercial banks operating in Indonesia between 2019 and 2024, generating approximately 12,000 observations. Using panel data estimation with fixed and random effects models, this study finds that exchange rate volatility significantly affects bank performance. Specifically, exchange rate movements have a stronger and more consistent impact on intermediation (LDR) than on profitability (INCSD), as indicated by a higher R-squared value (0.9561 for LDR compared to 0.5309 for INCSD), which aligns with findings from Syarifuddin and Haryanto (2023) and Ghosh (2020). Keywords: Exchange rate, bank performance, panel estimation, intermediation, profitability.